Mycobiome analysis of asymptomatic and symptomatic Norway spruce trees naturally infected by the conifer pathogens Heterobasidion spp. Issue 5 (3rd September 2018) - Kovalchuk, Andriy; Mukrimin, Mukrimin; Zeng, Zhen; Raffaello, Tommaso; Liu, Mengxia; Kasanen, Risto; Sun, Hui; Asiegbu, Fred O.
Summary: Plant microbiome plays an important role in maintaining the host fitness. Despite a significant progress in our understanding of the plant microbiome achieved in the recent years, very little is known about the effect of plant pathogens on composition of microbial communities associated with trees. In this study, we analysed the mycobiome of different anatomic parts of asymptomatic and symptomatic Norway spruce trees naturally infected by Heterobasidion spp. We also investigated the primary impact of the disease on the fungal communities, which are associated with Norway spruce trees. Our results demonstrate that the structure of fungal communities residing in the wood differed significantly among symptomatic and asymptomatic Heterobasidion ‐infected trees. However, no significant differences were found in the other anatomic regions of the trees. The results also show that not only each of individual tree tissues (wood, bark, needles and roots) harbours a unique fungal community, but also that symptomatic trees were more susceptible to co‐infection by other wood‐degrading fungi compared to the asymptomatic ones.